Black or Right Anti/Racist Campus Rhetorics - Maraj, Louis M. (University Press of Colorado, 2020)
emBlack or Right: Anti/Racist Campus Rhetorics/em explores notions of Blackness in white institutional-particularly educational-spaces. In it, Louis M. Maraj theorizes how Black identity operates with/against ideas of difference in the age of #BlackLivesMatter. Centering Blackness in frameworks for antiracist agency through interdisciplinary Black feminist lenses, emBlack or Right/em asks how those racially signifying "diversity" in US higher education (and beyond) make meaning in the everyday. Offering four Black rhetorics as antiracist means for emrhetorical reclamation/em-autoethnography, hashtagging, inter(con)textual reading, and reconceptualized disruption-the book uses Black feminist relationality via an African indigenous approach. Maraj examines fluid, quotidian ways Black folk engage anti/racism at historically white institutions in the United States in response to violent campus spaces, educational structures, protest movements, and policy practice. emBlack or Right/em's experimental, creative style strives to undiscipline knowledge from academic confinement. Exercising different vantage points in each chapter-autoethnographer, digital media scholar/pedagogue, cultural rhetorician, and critical discourse analyst-Maraj challenges readers to ecologically understand shifting, multiple meanings of Blackness in knowledge-making. emBlack or Right/em's expressive form, organization, narratives, and poetics intimately interweave with its argument that Black folk must continuously invent "otherwise" in reiterative escape from oppressive white spaces. In centering Black experiences, Black theory, and diasporic Blackness, emBlack or Right/em mobilizes generative approaches to destabilizing institutional whiteness, as opposed to reparative attempts to "fix racism," which often paradoxically center whiteness. It will be of interest to both academic and general readers and significant for specialists in cultural rhetorics, Black studies, and critical theory.